The effect of ion-exchange stabilizer and cement amount on improved road subgrade soil laboratory specimens compressive strength and resistance to frost - Vaitkus, Audrius; Kilaitė, Deimantė; Mickevič, Rafal; Šernas, Ovidijus (International Conference “Environmental Engineering”, 2023)
especially in roads that are sensitive to moisture fluctuations and frost. To improve the performance of weak soils, usually treatment with cement or lime is applied. However, in the most cases, treatment only with cement or lime only requires relatively high amount of these materials or do not ensure resistance to frost. Usually, to improve the performance of treated soils, various additives are applied. One of the most popular additives is ion-exchange stabilizers. However, the performance of additives depends on soil type and the composition of additive. The aim of this study is to evaluate the properties as compressive strength and resistance to frost of soil, treated with different additives. Research showed that the application of an ion-exchange stabilizer increases compressive strength of clay up to 12% and the compressive strength of sand up to 18%.